Synthesis of Jatropha curcas-based methyl ester and ethyl ester as biodiesel feedstocks - Yunus, Robiah; Mohd Ghazi, Tinia Idaty; Muhammad Syam, Azhari; Choong, Thomas Shean Yaw (Universiti Putra Malaysia Press, 2012)
Research on the use of Jatropha curcas triglycerides as biodiesel feedstock has received worldwide attention due to its inherent characteristics. Unlike palm oil, J. curcas oil is not edible, and thus, it will not disturb the food supply. However, to the researcher's experiences with the synthesis of J. curcas, oil-based biodiesel has shown that the fuel characteristics depend largely on the type of alcohol used as the excess reactants. Transesterification reaction is chosen for this process with sodium methoxide as the catalyst. Comparison studies on the yield of esters using methanol and ethanol, as well as the impacts on the reaction rate are discussed. The effects of reaction time and molar ratio on the reaction conversion are also examined. The determination of reaction yield is based on the conversion of triglycerides into alkyl esters as the main product. The findings are described as follows: the highest percentage yield of product is attained at 96% for methanol as an excess reactant, and this is 90% when ethanol is used. The optimum conditions of parameters are achieved at 6:1 molar ratio of alcohol to triglycerides, 50 min of reaction time and reaction temperature of 65Â°C for methanol and 75Â°C for ethanol. The biodiesel properties of both ester fuels were determined according to the existing standards for biodiesel and compared to the characteristics of diesel fuel.